PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISONS (STAD) BERBANTUAN KAHOOT TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI SMAN 12 PADANG - Josania, Bivany (Jurnal Edukasi dan Penelitian Matematika, 2023)
Learning outcomes are the results obtained by students after participating in learning, which are assessed by exams. But in fact the learning outcomes of class XI students of SMAN 12 Padang are still low. The solution is the application of cooperative learning models such as Student Teams Achievement Divisions. The purpose of this study was to describe the activities carried out by students while the STAD model was applied and how the Kahoot-assisted STAD model affected the learning outcomes of class XI students at SMAN 12 Padang. The type of research used is quasy experimental research and descriptive research with a non-equivalent posttest-only control group design. The population is students of class XI IPS SMAN 12 Padang. Instruments in the form of observation sheets and tests. Based on the observation results, it was found that the positive activity development of students increased with the STAD model, and based on data analysis, the Mann-Whitney test obtained p-values = 0.0000 <0.05, meaning  was rejected. Thus, the learning outcomes of students with the STAD model are better than the conventional learning model. In other words, the application of the kahoot-assisted STAD model increases the activity and learning outcomes of class XI students of SMAN 12 Padang. Keywords– Learning Achievement, STAD Model, Kahoot